MAINTENANCE PADA POMPA SENTRIFUGAL KEWPUMP - Ginting, Zefanya Karsten; Helmizar; Puspawan, Angky (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2024)
Kewpump centrifugal pump is a very important pump in PT. Incasi Raya Edible Oil, West Sumatra Province. Where the efficiency of this pomp greatly affects the performance of PT. Incasi Raya. The use of this centrifuga pump is to move CPO (Crude Palm Oil). This practical work report conveys information on kewpump centrifugal pump maintenance management. This pump works for 24 hours without stopping. Things that need to be done before maintenance are checking into the field, looking for the source of damage, recording the recurrence of the damage, taking data, asking for maintenance schedules. Usually damage to the pump in PT. Incasi Raya occurs due to mechanical seals, damaged bearings, impeller jams that will affect pump performance, so maintenance is carried out using the corrective maintenance method. Based on the maintenance activities carried out, the results were obtained that damage to the pump occurred in the mechanical seal, with moderate damage that was inspected periodically. Then it is necessary to carry out maintenance in accordance with the procedures that have been made.